Associação à positividade da Lawsonia intracellularis com a expressão clínico-patológica da infecção em suínos da região metropolitana de Bucaramanga (Santander, Colômbia) (2023)
Fragments of terminal ileum were collected from 100 pigs at slaughter from Bucaramanga Metropolitan Area (Santander, Colombia), to study the efficacy of the diagnosis of porcine proliferative enterophaty (PPE) through the technique of nested polymerase ch